The Policy Implementation Challenges of Individual Plans for Preschool Children with Disabilities - Cameron, David L.; Tveit, Anne D. (International Journal about Parents in Education, 2023)
This article presents findings from an investigation in southern Norway that sought to provide insight into diverse forms of collaboration on behalf of children with severe disabilities in preschool. The use of individual plans (IP) for preschool-age children is relatively new in Norway, and is being widely promoted as a tool for facilitating collaboration and support from multiple sectors. We employed a case study approach involving observations and semi-structured interviews with 5 members of the IP team supporting a 5 year-old girl with a severe disability. Using qualitative content analysis we determined relevant themes from transcribed interviews and field notes. Participants included the child’s mother and father, preschool teacher, special educator, and the municipal public health nurse who also acted as the IP coordinator. We conclude that in its current form the IP in this case had little relevance for participants and did little to contribute to providing this child with the individually adapted support that the policy was intended to facilitate.